Endolysins as antibacterial agents : from engineering approaches to the uncovering of holin as a key factor influencing lytic activity - Fernandes, Sofia (2016)
Tese de doutoramento, Farmácia (Microbiologia), Universidade de Lisboa, Faculdade de Farmácia, 2016